ASSESSMENT PERSPECTIVES OF BEGINNING NUMBER RELATED TUTORING - Prof. Dr. Risto Bojović (International Scientific and Current Research Conferences, 2023)
Based on the review conducted by the Worldwide Commission on Numerical Guidance, this paper examines the perspectives of showing calculation. We considered that the subjects of room and spatial thinking ought to be important for it as central points of interest, just as showing draws near, RME, learning through discovering numerical thoughts, the role of course readings in the underlying math training, etc., keeping in mind the current requirements in calculation instruction. As a result, this research paper provides a comprehensive understanding of our need to manage these points and welcomes analysts from the larger numerical community, who are informed of the results of our investigation in the field of beginning calculation instruction in Serbia.